Human coronary microvascular contractile dysfunction associates with viable synthetic smooth muscle cells. Issue 8 (26th June 2021) - Dora, Kim A; Borysova, Lyudmyla; Ye, Xi; Powell, Chloe; Beleznai, Timea Z; Stanley, Christopher P; Bruno, Vito D; Starborg, Tobias; Johnson, Errin; Pielach, Anna; Taggart, Michael; Smart, Nicola; et al.
Abstract: Aims: Coronary microvascular smooth muscle cells (SMCs) respond to luminal pressure by developing myogenic tone (MT), a process integral to the regulation of microvascular perfusion. The cellular mechanisms underlying poor myogenic reactivity in patients with heart valve disease are unknown and form the focus of this study. Methods and results: Intramyocardial coronary micro-arteries (IMCAs) isolated from human and pig right atrial (RA) appendage and left ventricular (LV) biopsies were studied using pressure myography combined with confocal microscopy. All RA- and LV-IMCAs from organ donors and pigs developed circa 25% MT. In contrast, 44% of human RA-IMCAs from 88 patients with heart valve disease had poor (<10%) MT yet retained cell viability and an ability to raise cytoplasmic Ca 2+ in response to vasoconstrictor agents. Comparing across human heart chambers and species, we found that based on patient medical history and six tests, the strongest predictor of poor MT in IMCAs was increased expression of the synthetic marker caldesmon relative to the contractile marker SM-myosin heavy chain. In addition, high resolution imaging revealed a distinct layer of longitudinally aligned SMCs between ECs and radial SMCs, and we show poor MT was associated with disruptions in these cellular alignments. Conclusion: These data demonstrate the first use of atrial and ventricular biopsies from patients and pigs to reveal that impaired coronary MT reflects a switch of viable SMCs towards a synthetic phenotype, rather than a loss of SMC viability. These arteries represent a model for further studies of coronary microvascular contractile dysfunction. Graphical Abstract: